3D Geological Modelling for Asmari Reservoir In Abu Ghirab Oil Field - Asad, Maaly S.; Hamd-Allah, Sameera M. (Iraqi Journal of Science, 2022)
Building a geological model is an essential and primary step for studying the reservoir’s hydrocarbon content and future performance. A three-dimensional geological model of the Asmari reservoir in Abu- Ghirab oil field including structure, stratigraphy, and reservoir petrophysical properties, has been constructed in the present work. As to underlying Formations, striking slip faults developed at the flank and interlayer normal. Abu Ghirab oilfields are located on the eastern anticlinal band, which has steadily plunged southward. 3D seismic interpretation results are utilized to build the fault model for 43 faults of the Asmari Formation in Abu Ghirab Oilfield. A geographic facies model with six different rock facies types are developed. This new modelling system should be capable of more clearly reflecting the connectivity of the oil body and the heterogeneity of the reservoir. To represent the vertical and horizontal heterogeneity and create a framework for the Asmari reservoir in the Abu Ghirab oil field, the Petrel software has been used to create a reservoir in a 3D model. This model was constructed using data from 55 wells located across the Asmari formation. The model demonstrates accurate estimations (porosity, saturation, and net to gross). These reservoir models directly impact the facies model’s computation of each layer of the net pay thickness of the reservoir. The final goal of the present work is to determine the initial oil in place (IOIP), which is found to be 269*106 sm3.